Isolated Lesser Trochanteric Fracture- A rare but possible clinical entity in adults - Syed Muhammad Mustahsan; Rizvi, Syed Hasan Mustafa (International Journal of Endorsing Health Science Research, 2015)
Isolated Trochanteric Fracture is a rare clinical entity in adults especially when it occurs due to trauma. Isolated traumatic fracture of lesser trochanter has been reported very rarely in the literature, as usually in adults, it is associated with malignancy which should be ruled out during the diagnosis.